Identiteternes møde, civilisationernes sammenstød? - Martijn van Beek (Religionsvidenskabeligt Tidsskrift, 2002)
Taking as its starting point Huntington’s thesis of a clash of civilisations, this article reviews anthropological critiques of primordialist conceptions of culture and identity as expressed in both cultural fundamentalist and multiculturalist understandings. The example of the Ladakh region of Jammu and Kashmir in India is used to show that multiplicity and syncretism are the very substance of practices of identification, even where clear and at times antagonistic divisions between religious communities are found. The assumption that xenophobia is a necessary or natural reaction to the encounter with others is therefore rejected as an expression of identity fetishism.